Validasi Psikometrik Skala Konflik Kerja-Keluarga pada Pasangan Berpenghasilan Ganda di Indonesia - Gumi Langerya Rizal; Priyalatha Govindasamy; Zulian Fikry (Jurnal Ilmu Perilaku, 2025)
Work–Family Conflict (WFC) has been widely examined, yet empirical validation of its measurement remains limited in Indonesia. Many local studies rely on translated instruments without comprehensive psychometric testing, raising concerns about cultural accuracy. This study addresses this gap by validating the bidimensional WFC scale, Work Interference with Family (WIF) and Family Interference with Work (FIW), among 492 dual-earner spouses in Indonesia. The results confirmed strong internal reliability (α > 0.78; CR > 0.85) and adequate convergent validity (AVE > 0.50), supporting a stable two-factor structure in which WIF and FIW emerged as related but distinct constructs. The findings highlight culturally embedded and gendered dynamics of role conflict in Indonesian couples and contribute to cross-cultural work–family research. Practically, the validated instrument provides a reliable tool for researchers and organizations to assess role conflict and develop family-supportive workplace policies.